The art of muscle biopsy in new genetic era - Nilipour, Yalda (Iranian Journal of Child Neurology, 2019)
Abstract Objective Muscle biopsy is a part of paraclinical workup of patients with neuromuscular diseases. With great new advances in techniques of molecular diagnosis like next generation sequencing (NGS) and introducing new serologic markers in recent years, the strategy of diagnosis of some neuromuscular diseases has been changed and application of muscle biopsy has been questioned in some instances. Materials and method We explain role of pre and post muscle biopsy factors and their importance to achieve the best result from a muscle biopsy and review indications of muscle biopsy in different types of neuromuscular diseases based on literature review and our 12 years experience as the only standard referral center for muscle biopsy for a population of about 80 millions. Conclusion Although diagnostic algorithm of some muscle diseases has been changed by recent advances in diagnostic biochemical and molecular techniques, still muscle biopsy continues to play a major role in diagnosis and managing of neuromuscular patients and physicians must choose their preferable diagnostic test for their patient’s, case by case, based on their local available facilities.